Harm reduction workforce, behavioral health, and service delivery in the USA: a cross-sectional study - Lisa de Saxe Zerden; Orrin D. Ware; Brooke N. Lombardi; Brianna M. Lombardi (BMC, 2024)
Abstract Background Despite recent financial and policy support for harm reduction in the USA, information on the types of workers within organizations who design, implement, and actualize harm reduction services remains nascent. Little is known about how variability in the harm reduction workforce impacts referrals and linkages to other community supports. This exploratory mixed-methods study asked: (1) Who constitutes the harm reduction workforce? (2) Who provides behavioral health services within harm reduction organizations? (3) Are referral services offered and by whom? (4) Do referrals differ by type of harm reduction worker? Methods Purposive sampling techniques were used to distribute an electronic survey to U.S.-based harm reduction organizations. Descriptive statistics were conducted. Multivariate binary logistic regression models examined the associations (a) between the odds of the referral processes at harm reduction organizations and (b) between the provision of behavioral health services and distinct types of organizational staff. Qualitative data were analyzed using a hybrid approach of inductive and thematic analysis. Results Data from 41 states and Washington, D.C. were collected (N = 168; 48% response rate). Four primary types of workers were identified: community health/peer specialists (87%); medical/nursing staff (55%); behavioral health (49%); and others (34%). About 43% of organizations had a formal referral process; among these, only 32% had follow-up protocols. Qualitative findings highlighted the broad spectrum of behavioral health services offered and a broad behavioral health workforce heavily reliant on peers. Unadjusted results from multivariate models found that harm reduction organizations were more than 5 times more likely (95% CI [1.91, 13.38]) to have a formal referral process and 6 times more likely (95% CI [1.74, 21.52]) to have follow-up processes when behavioral health services were offered. Organizations were more than two times more likely (95% CI [1.09, 4.46]) to have a formal referral process and 2.36 (95% CI [1.11, 5.0]) times more likely to have follow-up processes for referrals when behavioral health providers were included. Conclusions The composition of the harm reduction workforce is occupationally diverse. Understanding the types of services offered, as well as the workforce who provides those services, offers valuable insights into staffing and service delivery needs of frontline organizations working to reduce morbidity and mortality among those who use substances. Workforce considerations within U.S.-based harm reduction organizations are increasingly important as harm reduction services continue to expand.